Modelagem computacional de um acelerador linear e da sala de radioterapia para cálculo da dose efetiva em pacientes submetidos a tratamento de câncer de próstata - Medeiros, Marcos Paulo Cavaliere de (2018)
This work describes the development and validation, using the MCNP code, of a realistic computational model of a 10 MV VARIAN linear accelerator equipped with a highly detailed VARIAN HD120 multileaf collimator. Validation was achieved by comparing calculated percentage dose depths and lateral dose profiles with commissioning measurements (golden data) from the manufacturer. The 4 x 4 cm2 , 10 x 10 cm2 and 20 x 20 cm2 fields were considered. The same model was adapted for simulation of the linear accelerator operating at 6 MV and 18 MV. In-field and out-offield validations were done in all cases. The modeling was used with an anthropomorphic voxel phantom to calculate absorbed doses in organs and tissues of a patient undergoing a three dimensional conformational radiotherapy protocol. Finally, additional steel and lead shielding added to the primary belt of the radiotherapy room were simulated in order to assess their influence on the effective dose in a patient undergoing prostate radiotherapy. Results suggest that, under the simulated conditions, both materials used as additional shielding exert very small influence on the doses in the patient.